SINTESIS DAN KARAKTERISASI NUKLEOTIDA BERTANDA [α-32P]ATP - Rahman, Wira Yusril; Sarmini, Endang; Herlina, H.; Abidin, A.; Triyanto, T.; Hambali, H.; Nurbaiti, Santi (Universitas Andalas, 2019)
The utilization of nuclear technology in health sector with molecular techniques is increasingly developed today, especially in Indonesia. One of which is nucleotide compound marked with [α-32P]ATP, this compound has been used as tracer for deoxyribonucleic acid (DNA)/ ribonucleic acid (RNA) in the study of various physiological and pathological processes. [α-32P]ATP is synthesized through several stages of continuous reaction in one reaction vessel. It begins with synthesis of [γ-32P]ATP through an enzymatic reaction, using H332PO4 and ADP, and enzymes of lactate dehydrogenase, 3-phosphoglycerate phosphokinase and glyceraldehide 3-phospho dehydrogenase; followed by phosphorilation of 3’AMP with T4 polinucleotide kinase enzyme to produce 3’-[5’-32P]ATP. The result is hydrolyzed with nuclease P1 enzyme to produce [5’-32P]AMP. The unreacted [γ-32P] is degraded by the addition of hexokinase enzyme and glucose. At the final stage of the reaction, the [5’-32P]AMP is phosphorilated using phosphoenol-piruvat, piruvat kinase, and myokinase to produce [α-32P]ATP. The test results show that the every stage of reaction is characterized using TLC method, PEI cellulose paper as stationary phase and KH3PO4 0,5 M pH 3,5 as mobile phase. At the end of reaction, the yield of [α-32P]ATP reaches 71,7%, at Rf = 0,2.